2018
DOI: 10.3386/w24865
|View full text |Cite
|
Sign up to set email alerts
|

Health and Economic Activity Over the Lifecycle: Literature Review

Abstract: We systematically review the literature linking health to economic activity, particularly education and labor market outcomes, over the lifecycle. In the first part, we review studies that link childhood health to later-life outcomes. The main themes we focus on are in-utero exposures, birthweight, physical health and nutrition, mental health, and the environment. In the second part, we review studies of the impact of health on labor market success for adults. The main themes we focus on are the environment, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 101 publications
(156 reference statements)
0
24
0
Order By: Relevance
“…This suggests the possibility of particularly high economic returns from improving mental health among adolescents and young adults. Although longitudinal studies show a substantial correlation between mental illness among students and subsequent educational outcomes, there is little experimental evidence to date that treatment of depression or anxiety among adolescents leads to improved educational outcomes (99).…”
Section: Human Capital Accumulationmentioning
confidence: 99%
“…This suggests the possibility of particularly high economic returns from improving mental health among adolescents and young adults. Although longitudinal studies show a substantial correlation between mental illness among students and subsequent educational outcomes, there is little experimental evidence to date that treatment of depression or anxiety among adolescents leads to improved educational outcomes (99).…”
Section: Human Capital Accumulationmentioning
confidence: 99%
“…This study has examined the impact of the political context experienced prenatally on infant health in the United States. The indicators of infant health we examine provide the first observable measure of individual health and well-being (Behrman and Butler 2007; Conley et al 2003; Moster, Lie, and Markestad 2008; Prinz et al 2018). Our analysis extends pioneering research on the impact of the president’s party on infant mortality (Rodriguez 2019; Rodriguez et al 2014) by examining widely prevalent adverse birth outcomes that predict health and well-being over the entire life course.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Democratic presidents is substantial in terms of the population affected, resulting in thousands fewer preterm and small for gestational age births. Given the large costs of poor birth outcomes in the United States—both immediately after birth, over the individual life course, and even across generations (Almond, Chay, and Lee 2005; Almond and Currie 2011; Behrman and Rosenzweig 2004; Prinz et al 2018; Russell et al 2007)—these effects have implications spanning decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have studied the effects of wealth loss, employment transitions, health shocks, and household structure changes on finances, labor supply, consumption, and health trajectories in older households. 1 Because of their ubiquity, health shocks in particular have been the subject of a substantial body of research (see Prinz et al (2018) for a recent summary). Recently, there has also been growing interest in understanding the effects of wealth loss and job displacement among older Americans, as research has shown that the wealth and employment trajectories of older households were substantially and permanently impacted by the severe downturns in the housing, financial, and labor markets that occurred during the Great Recession of [2007][2008][2009] (Munnell and Rutledge, 2013).…”
mentioning
confidence: 99%